2008
DOI: 10.1086/589507
|View full text |Cite
|
Sign up to set email alerts
|

r -Process Nucleosynthesis in Hot Accretion Disk Flows from Black Hole-Neutron Star Mergers

Abstract: We consider hot accretion disk outflows from black hole-neutron star mergers in the context of the nucleosynthesis they produce. We begin with a three-dimensional numerical model of a black hole-neutron star merger and calculate the neutrino and antineutrino fluxes emitted from the resulting accretion disk. We then follow the element synthesis in material outflowing the disk along parameterized trajectories. We find that at least a weak r-process is produced, and in some cases a main r-process as well. The neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
194
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(198 citation statements)
references
References 27 publications
2
194
0
2
Order By: Relevance
“…Element synthesis in the hot outflows from merger-type black hole accretion disks has previously been addressed in, e.g., [17,18,19,20,21,22]. These found neutron-rich outflows to be possible in this environment, and thus suggested that merger-type disk winds may be an important source of particularly the lighter r-process nuclei.…”
Section: Introductionmentioning
confidence: 91%
“…Element synthesis in the hot outflows from merger-type black hole accretion disks has previously been addressed in, e.g., [17,18,19,20,21,22]. These found neutron-rich outflows to be possible in this environment, and thus suggested that merger-type disk winds may be an important source of particularly the lighter r-process nuclei.…”
Section: Introductionmentioning
confidence: 91%
“…Using the typical conditions in neutrino-driven winds from PNSs for comparison, we can identify promising r-process scenarios involving other types of CCSN ejecta based on whether they have lower Y e , higher S 0 , shorter τ dyn , or any combination of the above. Lower Y e can be obtained in winds from accretion disks (or tori) surrounding black holes that are formed in special CCSNe associated with long gamma-ray bursts [57,58] or in neutron star mergers associated with short ones [59,60]. The dense disk material is neutron rich due to electron capture and emits ν e with a harder spectrum than that of ν e .…”
Section: Other Scenarios Involving Ccsn Ejectamentioning
confidence: 99%
“…2.1.3). The neutron-rich torus surrounding black holes formed in these events might have neutrino-driven winds that can produce a significant amount of Sr (e.g., [59,60]). In any case, we characterize the H source with a fixed yield ratio (Sr/Ba) H .…”
Section: Implications and Constraints From Observationsmentioning
confidence: 99%
“…The nuclei that form are dependent on the accretion rate of the disk and on the neutrinos that are released from it [5]. Rapidly accreting disks characteristic of neutron star mergers are most likely to produce rapid neutron capture elements in hot outflows [6], while more slowly accreting disks are more likely to produce Nickel-56 or p-process elements [5,7,8]. Since the neutrinos are crucial for understanding the the nucleosynthetic products, in this contribution we consider two neutrino effects.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 shows a disk formed by a black hole neutron star merger, calculated in [6,9]. Above the disk, the emitted neutrinos interact with material outflowing from the disk through the reactions ν e + n → p + e − andν e + p → n + e + .…”
Section: Introductionmentioning
confidence: 99%